Human intrahepatic regulatory T cells are functional, require IL‐2 from effector cells for survival, and are susceptible to Fas ligand‐mediated apoptosis. Issue 1 (15th April 2016) - Chen, Yung‐Yi; Jeffery, Hannah C.; Hunter, Stuart; Bhogal, Ricky; Birtwistle, Jane; Braitch, Manjit Kaur; Roberts, Sheree; Ming, Mikaela; Hannah, Jack; Thomas, Clare; Adali, Gupse; Hübscher, Stefan G.; et al.
Abstract : Regulatory T cells (Treg ) suppress T effector cell proliferation and maintain immune homeostasis. Autoimmune liver diseases persist despite high frequencies of Treg in the liver, suggesting that the local hepatic microenvironment might affect Treg stability, survival, and function. We hypothesized that interactions between Treg and endothelial cells during recruitment and then with epithelial cells within the liver affect Treg stability, survival, and function. To model this, we explored the function of Treg after migration through human hepatic sinusoidal‐endothelium (postendothelial migrated Treg [PEM Treg ]) and the effect of subsequent interactions with cholangiocytes and local proinflammatory cytokines on survival and stability of Treg . Our findings suggest that the intrahepatic microenvironment is highly enriched with proinflammatory cytokines but deficient in the Treg survival cytokine interleukin (IL)‐2. Migration through endothelium into a model mimicking the inflamed liver microenvironment did not affect Treg stability; however, functional capacity was reduced. Furthermore, the addition of exogenous IL‐2 enhanced PEM Treg phosphorylated STAT5 signaling compared with PEMCD8. CD4 and CD8 T cells are the main source of IL‐2 in the inflamed liver. Liver‐infiltrating Treg reside close to bile ducts and coculture with cholangiocytes or their supernatants induced preferential apoptosis of Treg compared with CD8 effector cells. Treg from diseased livers expressed high levels of CD95, and their apoptosis was inhibited by IL‐2 or blockade of CD95. Conclusion : Recruitment through endothelium does not impair Treg stability, but a proinflammatory microenvironment deficient in IL‐2 leads to impaired function and increased susceptibility of Treg to epithelial cell‐induced Fas‐mediated apoptosis. These results provide a mechanism to explain Treg dysfunction in inflamed tissues and suggest that IL‐2 supplementation, particularly if used in conjunction with Treg therapy, could restore immune homeostasis in inflammatory and autoimmune liver disease. (Hepatology 2016;64:138–150)